The ambivalence of logistical connectivity: a co-research with Foodora Riders. (1st April 2019) - Leonardi, Daniela; Murgia, Annalisa; Briziarelli, Marco; Armano, Emiliana
Abstract : This article explores the notion of logistical connectivity as a twofold and ambivalent lens. On one hand, connectivity can be seen as a pervasive logistical tool for labour exploitation and surveillance. On the other, it opens up opportunities to establish new kinds of social relations and forms of worker organisation. The analysis draws on empirical data gathered during 2016 in Turin, a city in northern Italy, during mobilisations by Foodora workers. The findings show that logistical connectivity constitutes an unprecedented form of pervasive control, but - under certain conditions - can be shaken and reversed by workers and become a mode of mobilisation and self-organising.